2002
DOI: 10.1117/12.478631
|View full text |Cite
|
Sign up to set email alerts
|

<title>Laser destruction and treatment of rocks</title>

Abstract: Experimental study of destructive effect of laser radiation upon rock samples has been carried out. Continuous wave C02-laser of LT-1 type with power up to 5 kW was used in experiments. The main objective of the study was to find parameters for rock -laser radiation' system for the conditions close to real technological processes of cutting rock slits, removing rock blocks and drilling boreholes. The experiments resulted in quantitative indications for efficient destruction of the rocks (quartzite, sandstone, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Next, the authors studied laser destruction and treatment of four different rocks with a CO 2 laser using up to 5 kW of laser power. The results discussed the effect of power density on different rocks after laser radiation [ 22 ]. A further study observed the feasibility of cutting natural granite stones with a CO 2 laser using a response surface methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Next, the authors studied laser destruction and treatment of four different rocks with a CO 2 laser using up to 5 kW of laser power. The results discussed the effect of power density on different rocks after laser radiation [ 22 ]. A further study observed the feasibility of cutting natural granite stones with a CO 2 laser using a response surface methodology.…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome these drawbacks, laser technology seems to be a good choice since it has already demonstrated its capability to treat different building materials such as concrete, natural stones, tiles, and rocks [5]. For example, some authors have focused on surface texturing of concrete by laser scabbling [6][7][8] or in marble [9]. Regarding granite, a polished surface was laser treated to be transformed into a non-slip surface by generating micro-craters [10,11] on it.…”
Section: Introductionmentioning
confidence: 99%
“…Laser cutting of granite by CO 2 laser was recently reported in [17]. Drilling of granite submerged in water [18] and surface treatment [9] has also been carried out by CO 2 lasers.…”
Section: Introductionmentioning
confidence: 99%